AS POLÍTICAS LINGUÍSTICAS VOLTADAS PARA O ENSINO DA LÍNGUA PORTUGUESA AOS IMIGRANTES QUE BUSCAM REFÚGIO EM CAMPO GRANDE-MS - LARISSA SILVA PEREIRA (2022)
In the year 2018 alone, more than eighty thousand requests for recognition of refugee status were verified in Brazil; the majority were migrants from Venezuela. The crisis scenario in that country caused its inhabitants to migrate to other regions in search of better living conditions. Mato Grosso do Sul is not the Brazilian state with the highest concentration of refugees, however, it presents an extremely significant number of this population. Although there are laws that guarantee the full citizenship of immigrants and refugees, as is the case of Law No. 13,445 of May 24, 2017 and Law No. 9,474 of July 22, 1997, one can see how difficult it is for these individuals to integrate, in fact, into the host society. In Brazil, besides financial problems, many of them arrive with no or little knowledge of the Portuguese language and, consequently, face countless difficulties in social and professional integration. At this juncture, this work presents quantitative and qualitative data about immigration on Brazilian soil and, especially, in the region of South Mato Grosso; and aims to investigate and analyze the projects, especially those in force in the city of Campo Grande, which aim to teach the Portuguese language to international migrants and refugees present in the state. The theoretical framework for the development of the research is present in the studies of Berger (2015), Calvet (2007), Grosso (2010), Lagares (2013), Maher (2013), Rajagopalan (2013), Severo (2013), among others. The study, which is linked to the research line: Description and linguistic analysis, will comprise the following stages: selection of the corpus, which will be developed during the research, exposure and discussion of the theoretical framework, analysis and description of the results obtained. Key-words: language policy; Venezuelan and Haitian refugees; portuguese language.